The Role of E- Management in Developing Administrative Work in Public Schools and the Ajloun Governorate Education Directorate from the Point of View of Administrators - Almomani, Huda Humaidan Saleem (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the role of E- management in developing administrative work in public schools and the Ajloun Governorate education directorate from the point of view of administrators, the researcher used the Descriptive approaches, study population consisted of all of all government school principals and administrators in the Directorate of Education of Ajloun Governorate, whose number is (272) administrators Female and male, the sample consist from (66) Female and (54)male, chosen randomly, to collect data Questioner used, which consisted (23) paragraph, the result of SPSS analysis shown that the level of the role of E- management in developing administrative work in public schools and the Ajloun Governorate education directorate from the point of view of administrators was moderated , The finding also showed there wasn’t any statistically significant differences at (α≤0.05) refers to administrator sex (male and female). In addition, there were statistically significant differences between the years of administrator experience in favor of (10 years and less), and there were statistically significant differences refers to workspace in favor of school.